Sustainable agriculture in the Cameron Highlands, Malaysia - Barrow, C.J. (School of Humanities, Universiti Sains Malaysia, 2016)
The Cameron Highlands are `at risk`, especially from environmentally damaging farming, insensitive building, and some forms of tourism development. Present day farming activities are unsustainable and are already degrading, or are soon likely to damage tourism, biodiversity, hydropower generation, and the quality of life of many people in the highlands and in the surrounding lowlands. The impacts of highland development are increasingly felt further afield, especially through the degradation of the water quality and flow regime of streams, which run to surrounding lowlands. Opportunities should be grasped to develop more sensitive agriculture, tourism, forest product extraction, and building strategies. The established farming, tourism, building, and forest product extraction are profitable. Understandably those involved and various institutions will hesitate to initiate changes which could reduce profitability, however, without some reinvestment and control the longer term prospects are for economic decline and serious environmental damage. More awareness of global and regional environmental change is also desirable. Because impacts are felt accross broad swathes of the lowlands it is in the interests of the Federal Government and surrounding States to invest in Cameron Highlands improvements. Unfortunately, the lowland `offsite` impacts are effectively hidden from those causing them, and people in the lowlands have yet to link their welfare with environmental management of highlands. A key step will be to present the full costs (including lowland impacts) in a way that can be compared with the financial benefits of current farming tourism and building. Opportunities must be grasped to prompt better environmental management and to pursue sustainable development. Somehow, those involved in farming, tourism, and forest product extraction have to be encouraged and supported to adopt sustainable, less damaging alternatives (Barrow, in press, Barrow, et al., 2004). One possibility is to encourage `dovetailing`- integrated development of activities, which are mutually supportive. There appears to be potential for farmers, tourism developers, those concerned with biodiversity conservation, and Orang Asli peoples involved in forest product extraction to work together toward sustainable development.